A Computational Study of Anticancer Activity of Curcumin Derivatives Using in silico Drug Designing and Molecular Docking Tools - Shefrin, S.; Manakadan, Asha Asokan; Saranya, T.S. (Asian Journal of Chemistry, 2018)
Cancer is an abnormal growth of cells beyond a defined area. Curcumin, the principal curcuminoid of turmeric (Curcuma longa), have wide therapeutic uses like anti-inflammatory, antitumor activities, etc. The present study aims to propose anticancer activity of 11 curcumin derivatives which include curcubitacin E, demethoxycurcumin, bisdemethoxycurcumin, α-elemene, (-) β-elemene, (-)δ-elemene, (-) γ-elemene, germacrone, curdione, furanodiene, calebin A and aromatic turmerone, against a standard drug, megestrol acetate used for the treatment of endometrial cancer, using computer aided drug designing (CAAD). The computational studies include calculation of bioactivity scores, molecular properties, analysis of primary and secondary structure of protein, toxicity prediction using various online tools including admetSAR, Pass Server, PepDraw, RaptorX, Molinspiration, ChemSketch and SwissPDB. The docking score of 11 ligands and Megestrol acetate was found using ArgusLab 4.0.1. It was interpreted that these molecules could be a great lead for further development of anticancer drug against the disease.